2011
DOI: 10.1002/cncr.26151
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic influence of metformin as first‐line chemotherapy for advanced nonsmall cell lung cancer in patients with type 2 diabetes

Abstract: BACKGROUND:It has been reported that antidiabetic drugs affect the risk of cancer and the prognosis of patients with diabetes, but few studies have demonstrated the influence of different antidiabetic agents on outcomes after anticancer therapy among patients with cancer. The objective of this study was to evaluate the influence of the antidiabetic drugs metformin and insulin on the prognosis of patients with advanced nonsmall cell lung cancer (NSCLC) plus type 2 diabetes who received first‐line chemotherapy.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
124
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(141 citation statements)
references
References 55 publications
(73 reference statements)
10
124
3
1
Order By: Relevance
“…This is an example of an effect modification (although in this example the authors did not formally test for an interaction). Furthermore, two recently published studies have found similar beneficial effects of metformin among patients with colorectal cancer and diabetes [72], and among patients with advanced non-small-cell lung cancer undergoing first-line chemotherapy [73].…”
Section: Effects Of Glucose-lowering Treatments On Cancer Treatmentsmentioning
confidence: 79%
“…This is an example of an effect modification (although in this example the authors did not formally test for an interaction). Furthermore, two recently published studies have found similar beneficial effects of metformin among patients with colorectal cancer and diabetes [72], and among patients with advanced non-small-cell lung cancer undergoing first-line chemotherapy [73].…”
Section: Effects Of Glucose-lowering Treatments On Cancer Treatmentsmentioning
confidence: 79%
“…In a retrospective casecontrol study, Mazzone and colleagues (31) found that metformin was associated with a more aggressive lung cancer phenotype and worse prognosis. Conversely, two observational studies, a small Chinese study with patients with lung cancer and a larger UK study that included many cancer types, showed that metformin was associated with improved survival in patients with lung cancer (17,18). A major limitation of these studies is the lack of adjustment for baseline patient characteristics that might account for metformin use.…”
Section: Discussionmentioning
confidence: 99%
“…One small retrospective study from China showed that patients with diabetes with lung cancer treated with metformin had improved overall and progression-free survival (18). However, the effect of metformin on lung cancer outcomes has not been validated in larger samples.…”
Section: At a Glance Commentarymentioning
confidence: 99%
“…Some, but not all [8] have reported improvements in progressionfree survival [9] and disease-free survival [10,11] but these investigations were limited by small sample sizes [8][9][10][11], drug exposure determined at limited numbers of time-points [8][9][10][11] and a lack of adjustment for important baseline patient characteristics [9]. Other studies have investigated metformin use and overall survival [12][13][14], but these results could reflect mortality from non-cancer causes.…”
Section: Introductionmentioning
confidence: 99%